INSECTS ASSOCIATED WITH THE GROUND OF A TROPICAL MANGROVE - MANZANO, M.R.; VARGAS, H.; CANTERA, J. (Revista Colombiana de Entomología, 1989)
Several aspects concerning the mangrove ecosystem of the Colombian pacific coast have been studied previously, mainly in relation to its vegetational systematics and to some of the organisms that inhabit it (fishes, mollusks, crustaceans, echinoderm). However, there is no information in the literature about the insects of this region. In this work, information was obtained about mangrove soil-inhabiting insects, especially the importance of Collembola in the litter decomposition process. Insects were collected using pitfall traps and were separated from litter by Berlese-Tullgren funnels. Collembola is the dominant group; the type of soil and litter are key determinant elements of its stratification pattern. In a polluted mangrove ecosystem, specific diversity is lower than that of a less polluted one, probably because of the abundances in the former of a dominant species complex of Collembola, which exploit an oversupply of food coming from decomposition of remains of mangroves cut previously and from burning of terrestrial vegetation.